Comparative analysis of the role of healthcare beliefs on childhood vaccination uptake among parents in Malaysia and Singapore during the COVID-19 pandemic - Low, Jia Ming; Khoo, Erwin Jiayuan; Thong, Meow Keong; Soo, Chloe; Tran, Anh Phuong; Lee, Le Ye; Cheah, Fook Choe (Frontiers in Public Health, 2025)
IntroductionThe rollout of successful vaccination programs during the COVID-19 pandemic has been impeded worldwide by high rates of vaccine hesitancy. We investigated vaccine hesitancy rates in Malaysia and Singapore, and explored whether these rates were associated with parents’ health beliefs.MethodsA total of 226 Malaysian parents (MPs) and 635 Singaporean parents (SPs) participated in an online voluntary survey between November 2021 and August 2022.ResultsMPs were younger and had more children compared to SPs. SPs were more likely to have received the COVID-19 vaccine than MPs, and less likely to delay vaccinations for their children. SPs displayed greater trust in information about vaccines, their children’s doctors and healthcare authorities than MPs. Despite the similarities in ethnography and geographic proximity, the prevalence of perceived parental vaccine hesitancy was higher in Malaysia than in Singapore; this was associated with differences in healthcare beliefs.DiscussionBeyond educational campaigns, strengthening community-based healthcare support, addressing misinformation, and fostering transparent communication from healthcare authorities may further enhance parental trust in vaccine.